Limite de incorporação de ligas de selênio em nanofibras eletrofiadas de Ecovio® - Machado, Ederson Luís (2024)
The investigation into the incorporation of In10Se90 chalcogenide alloy into Ecovio® polymeric membranes produced by electrospinning aimed to evaluate the impact of this incorporation on the properties of the resulting composites and identify the limits of this process. Using analytical techniques such as FTIR, DSC, and TGA, the study assessed the influence of alloy concentration variation and ultrasound treatment on the structural, thermal, and physicochemical characteristics of the membranes. FTIR spectroscopy revealed no significant chemical interactions between Ecovio® and the In10Se90 alloy, indicating that ultrasound did not induce relevant structural changes in the polymer fibers. DSC analysis showed that the alloy incorporation had a limited effect on the melting and glass transition temperatures, with a slight impact on PLA cold crystallization. TGA analysis demonstrated that both alkaline treatment and the presence of the alloy affected the thermal stability of the membranes, with a reduction in the degradation temperature of PLA associated with increased reactivity of the polymer chains. These results highlight that the incorporation of In10Se90 presents clear limits in maintaining the structural and thermal properties of the polymer. The study provides a foundation for future research focused on optimizing the incorporation of semiconductors in electrospun polymers, aiming to develop composites with adjustable properties for applications in optoelectronic and photonic devices.